Molecular species delimitation and its implications for species descriptions using desmosomatid and nannoniscid isopods from the VEMA fracture zone as example taxa. (February 2018) - Brix, Saskia; Bober, Simon; Tschesche, Claudia; Kihara, Terue-Cristina; Driskell, Amy; Jennings, Robert M.
Abstract: We found 72 species for COI and 45 for 16 S by species delimitation among 186 (from 195 extracted) desmosomatid (144) and nannoniscid (42) sequenced specimens of a total of > 400 specimens for both families. Multiple "discovery"-type species delimitation methods were used, so that consistency across methods could be assessed: The ABGD analysis detected a barcode gap of 3–6% for COI and 4–6% for 16 S, in the whole dataset. Most putative species have a horizontally limited distribution along the Vema fracture zone, although the details depend in part on the interpretation of species delimitation analyses. Putative species were mostly restricted to the eastern or western Vema fracture zone, with only eight crossing the complete Vema fracture zone. Our data suggest that even robustly-sampled species exhibited small ranges; the range estimates calculable from present data were around 500 km, and three were on the order of 1000–2500 km. We chose an abundant, but geographically restricted species ( Eugerdella egoni Tschesche and Brix sp. nov.) collected at a single site in the Vema transform fault, and two species ( Prochelator barnacki Bober and Brix sp. nov. and Whoia sockei Brix and Kihara sp. nov.) with a broad, but disjunct distribution in the Vema fracture zone for taxonomic description.